PEMETAAN PERAN PEMANGKU KEPENTINGAN TERHADAP PENGAMBILAN KEPUTUSAN TERHADAP KETERBUKAAN DATA - Emigawaty Emigawaty; Ahmad Luthfi (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2021)
The role of stakeholders in government agencies in making decisions to disclose dataset in the public domain is very important and fully central. In Indonesia, government institutions are primary data providers and have the authority to determine which types of datasets may be disclosed to the public. Nevertheless, the decision-making process to open datasets carried out by government institutions is cumbersome and faces several challenges. At the same time, stakeholders can have different perspective on data disclosure, and therefore there can be pros and cons between them. Some of the causes of potential disputes in this decision making are because of several factors, such as differences in goal settings, interests, and requirements among stakeholders. The purpose of this study is to map the role of stakeholders in making data disclosure decisions. In order to map roles, this research involves several stakeholders from internal government institutions such as decision-makers, data analysts, and data evangelists. The results of this mapping indicate that each stakeholder proposes a unique blend of expertise, legitimacy, experience, risk-averse culture, as well as potential usefulness in making decisions to disclose data to the public domain. Based on the results of a case study using a semi-structured interview approach, it can be concluded that the decision-maker tends to consider the benefits and risks efficiency factors. Data analysts have an important role in weighing the benefits and risks. Meanwhile, data evangelists also play an essential role in in-depth technical analysis aspects to make stronger evidence-based or reference-based decision-making. This research contributes to providing the level of stakeholder involvement in the form of mapping roles and interests to change the current state of the stakeholder position to the desired state in the government strategic plan.